OPTIMALISASI PRODUKSI MICROGREEN SELADA (Lactuca sativa L.) MELALUI AIR KELAPA DAN KERAPATAN TANAMAN - Hidrawati, Hidrawati; Syam, Netty; Alimuddin, Suraedah; Khofifah, Nurul (Percetakan Umi Toaha Makassar, 2025)
This study was conducted with the aim of 1) analyzing the effectiveness of coconut water on the production of microgreen lettuce. 2) to get the optimal plant density level in producing microgreen lettuce. 3) To analyze the interaction of coconut water and plant density on microgreen lettuce production. The research was conducted at Fresco Organic Farm, Paccellekang Village, Patallassang District, Gowa Regency, South Sulawesi Province. The research took place from May to August 2024. This study used a completely randomized design (CRD) two-factor factorial pattern. The first factor is coconut water with four levels of treatment, namely without coconut water (Control), coconut water 100 ml, 200 ml, and 300 ml. The second factor is the plant density level with three treatment levels, namely 100 seeds, 150 seeds, and 200 seeds. 12 treatment combinations were repeated three times, resulting in 36 experimental units. The parameters observed were plant height, number of leaves, fresh weight, fresh weight of consumption, and protein content. The results showed that applying coconut water as much as 100 ml gave the most effective results on plant height of 7.29 cm, fresh weight of 8.42 g, and fresh weight of consumption of 7.64 g. Plant density level produced the best effect on plant height. The level of plant density produced the best effect on plant height, which was 7.14 cm, fresh weight of 9.27 g, and fresh weight of consumption of 8.35 g. The interaction of coconut water and plant density resulted in the best effect on plant height. The interaction of coconut water and plant density level had no significant effect on the production of microgreen lettuce.